Use of a flexible wall permeameter to study the hydraulic properties of tropical soils from a municipal solid waste disposal site - Yacoub, J. D. [UNESP]; Rodrigues, R. A. [UNESP]; Mondelli, G. [UNESP]; Giacheti, H. L. [UNESP] (My University, 2023)
The inadequate disposal of municipal solid waste (MSW) is a global problem, particularly in developing countries. This scenario can lead to soil and water contamination by leachate, such as the Bauru MSW landfill in Brazil, which has an identified contamination plume and may reach possible water supply sources in Bauru. In this context, the direction of the contamination plume depends on the hydraulic characteristics of the soil and rock. The hydraulic conductivity (k) of a tropical sandy soil profile representative of the Bauru MSW landfill was studied together with the bedrock (sandstone) using a flexible wall permeameter at average effective stresses close to the in situ values, i.e., 20, 40, 80, 160 and 320 kPa. The unsaturated hydraulic conductivity was estimated by the soil water retention curve (SWRC). Disturbed and undisturbed soil samples were collected at 1, 4, 7, 11, 13, and 16 m depth at the experimental research site of Unesp-Bauru. The sandstone samples were collected from a rock outcrop at the Bauru MSW landfill. The results indicated a decrease of hydraulic conductivity by 43% for 1 m depth, 29% for 4 m depth, 46% for 7 and 11 m depth, 61% for 13 and 16 m depth, and 96% for sandstone under 320 kPa of confinement pressure. Based on SWRC, the soil and sandstone results suggest using the saturated hydraulic conductivity for further analyses concerning the Bauru MSW landfill.
Keywords: Bauru MSW landfill; flexible wall permeameter; hydraulic conductivity; sandstone; tropical soils